2020
DOI: 10.1097/j.pain.0000000000001896
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled study of daily cannabidiol for the treatment of canine osteoarthritis pain

Abstract: Over the last 2 decades, affirmative diagnoses of osteoarthritis (OA) in the United States have tripled due to increasing rates of obesity and an aging population. Hemp-derived cannabidiol (CBD) is the major nontetrahydrocannabinol component of cannabis and has been promoted as a potential treatment for a wide variety of disparate inflammatory conditions. Here, we evaluated CBD for its ability to modulate the production of proinflammatory cytokines in vitro and in murine models of induced inflammation and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(168 citation statements)
references
References 58 publications
9
155
0
4
Order By: Relevance
“…injection of lipopolysaccharide (LPS), Verrico et al demonstrated that CBD diminished serum levels of pro-inflammatory factors interleukin 6 (IL-6) and tumor necrosis factor α (TNFα) and increases levels of the anti-inflammatory cytokine interleukin 10 (IL-10). Similar results Verrico et al were obtained in an in vitro model of inflammation in the same study [ 81 ]. On the other hand, Britch et al demonstrated that twice daily i.p.…”
Section: The Analgesic Potential Of Cbdsupporting
confidence: 90%
See 1 more Smart Citation
“…injection of lipopolysaccharide (LPS), Verrico et al demonstrated that CBD diminished serum levels of pro-inflammatory factors interleukin 6 (IL-6) and tumor necrosis factor α (TNFα) and increases levels of the anti-inflammatory cytokine interleukin 10 (IL-10). Similar results Verrico et al were obtained in an in vitro model of inflammation in the same study [ 81 ]. On the other hand, Britch et al demonstrated that twice daily i.p.…”
Section: The Analgesic Potential Of Cbdsupporting
confidence: 90%
“…In preclinical models, CBD exerts an analgesic effect via different routes of administration. In a spontaneous canine OA model, CBD increased dogs’ mobility and reduced pain, while no side effects were observed, Gamble et al demonstrated increased alkaline phosphatase during CBD treatment [ 81 , 86 ]. In rodent OA models, disease is usually induced by intra-articular (i.a.)…”
Section: The Analgesic Potential Of Cbdmentioning
confidence: 99%
“…Potential explanations for variable, and often poor, CBD absorption have pertained to properties of the CBD itself (e.g., poor water solubility) and also variability brought about by the significant first pass metabolism it must endure following oral ingestion. To counter these potential absorption hurdles, CBD preparations have been modified, with mixed success, in a variety of ways, including generation of synthetic CBD [20], creation of water-soluble CBD powders [12], development of self-emulsifying delivery systems [18,20], and encapsulation of CBD within gelatin matrix pellets [21] and liposomes [22]. One important consideration when evaluating CBD formulations is the pharmacokinetic goal and intended use of the CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis -derived herbal extracts (CHEs) are increasingly popular for both human and animal use, with recent legalization of such products in Canada and some European countries and American states. There is significant interest in evaluating CHE products for a variety of applications in both human and animal health, including chronic osteoarthritis ( 1 , 2 ), epilepsy ( 3 , 4 ), neuropathic pain ( 5 ), and nausea/emesis ( 6 ). Substantial differences can exist between CHE formulations produced by licensed vs. unlicensed producers, with wide variations in cannabinoid composition and label accuracy ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%